Deadly cargo - Bailey, Jodie (Love inspired suspense., 2021)
"Following an anonymous tip, K-9 Trooper Will Stryker's drug-trafficking investigation has a new suspect - Jasmine Jefferson, an Alaskan bush pilot he's convinced is hiding something. But when someone tries to kill them, Jasmine confesses she's in witness protection. Now Will and his K-9 partner, Scout, must work with Jasmine to figure out if the attacks are related to his case ... or if someone's out for revenge." -- Back cover.